Pengembangan Mobile Learning Application Berbasis Android untuk Mengajarkan Pemodelan Matematika pada Materi Pertidaksamaan Linear Satu Variabel - Sugandi, Oktavia Wahyu; Palupi, Evangelista Lus Windyana; Hidayat, Dayat (MATHEdunesa, 2024)
One Variable Linear Inequalities (PtLSV) material is one of the materials in mathematics that is related to real problems. In reality, there are still many students who have difficulty solving PtLSV, especially doing mathematical modeling of PtLSV problems. Mathematical modeling is the process of transforming real problems into the form of a mathematical model. One effort that can support the teaching of mathematical modeling is using learning media in the form of an Android-based mobile learning application. This study aims to describe the process of developing a mobile learning application based on Android to teach mathematical modeling in the PtLSV material and to describe the results of developing a mobile learning application based on Android to teach mathematical modeling in the PtLSV material that are valid, practical, and effective. This research uses the ADDIE development model consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Research instruments used include validation sheets, student response questionnaires, pre-test, and post-test. This media was validated by three validators consisting of media experts and material experts. Media trials were conducted on seventh-grade students at SMP Negeri 8 Surabaya in one class. Based on the research results, the developed learning media meets the valid criteria based on media experts at 3,65, which falls into the valid category, and material experts at 3,59, which also falls into the valid category. It meets practical criteria based on the response questionnaire at 3,31, which falls into the very good category, and meets effective criteria based on pre-test and post-test with an average N-Gain Score of 0,96, which falls into the high category.